Spatial simulation of water use efficiency in a Mediterranean environment - Rinaldi M.; Ubaldo R. (Water saving in Mediterranean agriculture and future research needs [Vol. 1], 2007)
Simulation models are often used to verify the potentiality of crop management, allowing multi-year and multi-location runs with minimum time spending. In Southern Italy, where water-limited conditions are frequent, is important to identify crop management which allows better the transformation of water (and irrigation water) in commercial yield. In this research a spatial analysis of a long-term simulation was carried out with AEGIS/WIN, a Geographic Information Systems (GIS) interface of DSSAT crop simulation package. The case-study is referred to a 1000 km2 area (Foggia, Southern Italy), characterized by 481 soil samples collected at a regular grid. Durum wheat and processing tomato have been simulated punctual-based using soil and long-term weather data (45 years). The two crops have been compared in the following management scenarios: rainfed and three automatic irrigation levels based on soil water content thresholds. Average and standard deviation of commercial yield (grain and fruit), seasonal evapotranspiration and irrigation amount were evaluated as model output. Water use efficiency (WUE) and irrigation water use efficiency (IRWUE) were then calculated. All the above variables were visualised and mapped with GIS. The wheat productivity was increased by irrigation of 19 percent and no difference occurred among automatic irrigation thresholds. WUE resulted similar in the 4 irrigation scenarios, while the southern part of the plain showed the higher IRWUE. In tomato the irrigation increased 3 times the yield respect to rainfed, with no difference among irrigation scenarios. WUE did not differ spatially, while IRWUE was higher in the southern part. Climatic conditions (rainfall and temperature) and soil water holding capability resulted the variables that more influenced the above use efficiencies, especially for tomato crop.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)